Nano-ranged low-energy ion-beam-induced DNA transfer in biological cells - Yu L.D. (2014)
Low-energy ion beams at a few tens of keV were demonstrated to be able to induce exogenous macromolecules to transfer into plant and bacterial cells. In the process, the ion beam with well controlled energy and fluence bombarded living cells to cause certain degree damage in the cell envelope in nanoscales to facilitate the macromolecules such as DNA to pass through the cell envelope and enter the cell. Consequently, the technique was applied for manipulating positive improvements in the biological species. This physical DNA transfer method was highly efficient and had less risk of side-effects compared with chemical and biological methods. For better understanding of mechanisms involved in the process, a systematic study on the mechanisms was carried out. Applications of the technique were also expanded from DNA transfer in plant and bacterial cells to DNA transfection in human cancer cells potentially for the stem cell therapy purpose. Low-energy nitrogen and argon ion beams that were applied in our experiments had ranges of 100 nm or less in the cell envelope membrane which was majorly composed of polymeric cellulose. The ion beam bombardment caused chain-scission dominant damage in the polymer and electrical property changes such as increase in the impedance in the envelope membrane. These nano-modifications of the cell envelope eventually enhanced the permeability of the envelope membrane to favor the DNA transfer. The paper reports details of our research in this direction. © 2013 Elsevier B.V.